An Empirical Investigation of the Impact of Bank Lottery Prices on Bank Performance - Abu Khalaf, Bashar; Alnabulsi, Khaleel (Jordan Journal of Business Administration, 2019)
The aim of this study is to empirically investigate the role of lottery prices, as a depositor marketing tool, on the performance of Jordanian commercial banks. It is of high interest for academics and specialists in finance and marketing, as well as for investors, to study the implications of lottery prices on the general performance of banks, measured by net interest margin and return on assets. Thirteen commercial banks in Jordan were enrolled in this study between the years 2000 and 2016. The results of this study show that lottery prices had a positive impact on the performance of banks, whereas bank efficiency was negatively affected by lottery prices during the period under investigation. The study concluded that customers are paying the extra cost of lottery prices provided by banks in the form of increased net interest margin.